Risks and management of hypertension in cancer patients undergoing targeted therapy: a review - Xiaolei Zhu; Shenhong Wu (BMC, 2022)
Abstract Background Rapid progress over the last decade has added numerous agents targeting specific cellular signaling pathways to the treatment armamentarium for advanced cancer. However, many of these agents can cause hypertension resulting in major adverse cardiovascular event. Methods and results A systematic literature search was performed on the databases PubMed and Google Scholar for papers published in English until December 2020. This review summarizes the risk, mechanism, diagnosis, and management of hypertension in cancer patients undergoing targeted therapy. The risk and pathogenesis of hypertension vary widely with different classes of targeted agents. Currently there is a paucity of data investigating optimal management of hypertension with targeted therapy. A practical approach is discussed with a focus on the goal of blood pressure control as well as drug selection based on the mechanism of hypertension in the context of advanced cancer, treatment toxicity, comorbidity, and drug-drug interactions. This review also discusses many studies that have explored hypertension as a biomarker for cancer treatment efficacy and as a pharmacodynamic biomarker to titrate drug dose. Conclusions The diversity of targeted agents has provided important insights into the pathogenesis of hypertension in cancer patients. The underlying mechanism may provide a guidance to the management of hypertension. Further studies are needed to investigate optimal treatment and hypertension as a biomarker for cancer treatment.